PENGARUH GAYA BELAJAR DAN DISIPLIN SISWA TERHADAP PRESTASI BELAJAR KORESPONDENSI SISWA KELAS X SMK NEGERI 1 TANJUNG PURA TAHUN AJARAN 2018/2019 - Nelly Armayanti; Elsa Sabrina Harahap (Prodi Pendidikan Administrasi Perkantoran UNIMED, 2020)
The purpose of this study are: 1) the influence of learning styles on correspondence learning achievement, 2) the influence of student’s discipline on correspondence learning achievement, 3) the influence of student learning styles and discipline on the correspondence learning achievement of class X AP students of SMK Negeri 1 Tanjung Pura TA 2018/2019. This research was held at SMK Negeri 1 Tanjung Pura with a population of 102 students and a sample of 50 students. The instrument used to measure student learning styles and disciplines in the form of questionnaires and to measure student learning achievement of students' correspondence is used the student’s correspondence scores of class X AP students of SMK Negeri 1 Tanjung Pura T.A 2018/2019. The data technique analysis is use multiple linear regression and to test the hypothesis.The results of data analysis obtained multiple regression equations is Y = 36,739 + 0,217 X1 + 0,337 X2 + e. The results of the t-test obtained by tcount = 4.646 with a significant level of 0,000 <0.05 for hypothesis 1 and for hypothesis 2 obtained tcount = 5,008 with a significant level of 0,000 <0,05. While simultaneous hypothesis testing obtained Fcount = 45,849 with a significan level of 0,000<0,05